Heidegger's Dasein: Development of the Ancient Greek Ontological Ideas of Being and Death - Wong, Lucas (Transactions on Social Science, Education and Humanities Research, 2024)
The primary objective of this article is to investigate the relationship between death and existence in philosophical systems that date back to ancient times and continue to exist in the present day. First, it will investigate the origins of the definition of existence, and then it will proceed to conduct an analysis of the philosophical advancements that occurred during the time period of the ancient Greeks. Last but not least, it will investigate Heidegger's viewpoint on existence and contrast it with the concepts that were prevalent among the ancient Greeks. This approach achieves a number of conceptual comparisons and analytical work by combining the ontological philosophy tradition with other philosophical traditions. There is Heidegger's concept of death, which is interpreted and compared textually as an important phenomenological text and tradition of thought. This is one of the examples. The finalization of its conclusions lies in the succession and development between the concept of death in phenomenological existentialism and the traditional metaphysical tradition. This is accomplished by organizing its work and the concept of death in his early period, and later lines of thought. The specific threads that are presented in this study will be beneficial to future scholarly work that is reflective on death from the perspective of the development of ideas in the tradition.